Statue Park: monuments from the communist dictatorship. F.l.t.r. Szamuely (Farkas), Kun (Olczai), Landler (Herczeg) - Renselaar, Herman van,
Statue Park: monuments from the communist dictatorship. F.l.t.r. Szamuely (Farkas), Kun (Olczai), Landler (Herczeg).